2019
DOI: 10.1021/acs.orglett.8b04035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Catalytic Staudinger Ligation

Abstract: Organophosphorus-catalyzed Staudinger ligation between carboxylic acids and azides in the presence of phenylsilane reductant produces amides. NMR-based mechanistic investigations revealed that the catalytic Staudinger ligation does not proceed via reduction of phosphine oxide but rather via reduction of iminophosphorane, which can subsequently undergo several transformations to produce the amide product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Mecinović later demonstrated an ambient temperature protocol by employing an optimized hydrosilane reductant . Catalytically formed iminophosphoranes from PPh 3 ( P11 ) can also be used for Staudinger amidation reactions (Figure B), although the precise mechanism of the redox cycle is unclear. …”
Section: State-of-the-art Developments In Organopnictogen Redox Catal...mentioning
confidence: 99%
“…Mecinović later demonstrated an ambient temperature protocol by employing an optimized hydrosilane reductant . Catalytically formed iminophosphoranes from PPh 3 ( P11 ) can also be used for Staudinger amidation reactions (Figure B), although the precise mechanism of the redox cycle is unclear. …”
Section: State-of-the-art Developments In Organopnictogen Redox Catal...mentioning
confidence: 99%
“…Undoubtedly, O’Brien’s 2009 report on a catalytic Wittig reaction, in which a silane reduces the phosphine oxide byproduct back to phosphine in situ during the reaction, unleashed the imaginations of researchers around the world . Consequently, the subsequent decade witnessed numerous accounts of catalytic versions of classical P­(V)O-generating reactions, including Wittig olefination, Appel reaction, Staudinger reduction, Staudinger ligation, aza-Wittig reaction, Mitsunobu reaction, and Cadogan cyclization, with all employing stoichiometric silanes as terminal reductants. , While studies of redox-driven phosphine oxide catalysis of the aforementioned reactions have continued, the past two years have been marked by the application of redox-driven phosphine oxide catalysis to lesser-known reactions.…”
Section: Phosphine Oxide Catalysismentioning
confidence: 99%
“…Denton demonstrated that the silane cannot be simply regarded as an innocent terminal reductant in these processes, 29 and subsequently White and Mecinović provided further mechanistic insight. 30…”
Section: Reviewmentioning
confidence: 99%